ANALYSIS OF TOURISM ATTRACTIONS, FACILITIES, HUMAN RESOURCES ON THE SATISFACTION OF TOURISTS VISITING AT PENATARAN BLITAR TEMPLE, EAST JAVA - Wibiyanto, Agung; Prastowo, Ichwan (STABN Raden Wijaya Wonogiri, 2023)
This study aims to analyze tourist attractions, facilities, human resources on the satisfaction of tourists visiting the Penataran Blitar temple, East Java. This research method is a quantitative study of multiple linear regression analysis, where the sample used in this study totaled 100 respondents throughout November 2022. While the data analysis method used is data validity test, data reliability test, correlation coefficient, and regression test . The results of this study showed a positive and significant effect of tourist attractions on visitor satisfaction at the Penataran temple by 31%. The better the tourist attractions in the Penataran temple, the more satisfied visitors will be in coming to the Penataran temple. There is a positive and significant influence of facilities on visitor satisfaction at the Penataran temple of 32.3%. The better the facilities at the Penataran temple, the higher the satisfaction of visitors coming to the Penataran temple. There is a positive and significant influence of human resources on visitor satisfaction at the Penataran temple by 35.8%. The better the human resources available at the Penataran temple, the more satisfied visitors will be in coming to the Penataran temple. The correlation coefficient value was obtained at 0.942. This means that there is a positive relationship between tourist attractions, facilities, and human resources on visitor satisfaction. The relationship between these variables is included in the very strong category. Thus tourist attractions, facilities, and human resources have a strong relationship to visitor satisfaction.